Subthreshold Electrical Noise Applied to the Plantar Foot Enhances Lower-Limb Cutaneous Reflex Generation - Sharma, Tushar; Peters, Ryan M.; Bent, Leah R. (Frontiers in Human Neuroscience, 2020)
Reflex responses generated by cutaneous mechanoreceptors of the plantar foot are important for the maintenance of balance during postural tasks and gait. With aging, reflex generation, particularly from fast adapting type I receptors, is reduced, which likely contributes to impaired postural stability in this population. Therefore, improving reflex generation from these receptors may serve as a tool to improve balance performance. A mechanism to enhance reflexes may lie in the phenomenon of stochastic resonance, whereby the addition of certain intensities and frequencies of noise stimuli improves performance of a system. This study was conducted to determine whether tactile noise stimuli could improve cutaneous reflex generation. In 12 healthy young adults we evoked cutaneous reflex responses using a 0-50 Hz Gaussian noise vibration applied to the plantar heel. Concurrently, we applied one of six subthreshold intensities of electrical tactile noise to the plantar heel (0%, 20%, 40%, 60%, 80% or 100% (threshold)) and were able to analyze data from 0%, 20% and 40% trials. Across participants it was found that the addition of 20% perceptual threshold (PT) noise resulted in enhanced reflex responses when analyzed in both the time and frequency domains. These data provide evidence that cutaneous reflex generation can be enhanced via a stochastic resonance effect and that 20% PT is the optimal intensity of noise to do so. Therefore, the addition of noise stimuli may be a valuable clinical intervention to improve reflex responses associated with postural balance in populations with impairments.